Dangerous detergent : dealing with the Tide Pod challenge - Robson, Karen, (SAGE Knowledge. Cases., 2019)
Tide (Procter & Gamble) is the best-selling detergent brand in the United States. In 2012, the brand introduced a very successful innovation to the market, the Tide Pod. In 2017, an Internet trend began in which teenagers would video themselves attempting to eat a Tide Pod and upload the video online. This activity is known as the "Tide Pod Challenge." Ingesting a Tide Pod has the potential to cause serious harm and can even be fatal. Students are asked how the Tide brand reacted to the public relations issues caused by the challenge.